Tinjauan Literatur: Keanekaragaman Jenis Flora pada Berbagai Ekosistem Hutan Tropis di Pulau Kalimantan: Literature Review: Flora Diversity in Various Tropical Forest Ecosystem On The Island Of Kalimantan - Juliyanti; Taqiyaturrohmah; Salsa Nabila Ramadhani (BiosciED: Journal of Biological Science and Education, 2025)
Kalimantan Island exhibits high plant diversity across various tropical forest ecosystems. This study aims to review previous research on plant species diversity in lowland rainforests, secondary forests, peat and swamp forests, and arboretums across Kalimantan. The method applied was a literature review of eleven national scientific articles published between 2015 and 2025. The results reveal a high diversity dominated by the families Dipterocarpaceae, Lauraceae, Myrtaceae, and Moraceae. Environmental factors such as humidity, light intensity, and soil conditions affect species distribution. Major threats include deforestation and habitat degradation; therefore, conservation efforts through arboretum establishment, phytochemical studies, and biodiversity-based education and ecotourism are essential to ensure sustainability.